Joint optimization for throughput fairness maximization in laser-powered UAV communications - Guolong Zhang; Qian Dan; Yutian Zhang (PLoS ONE, 2026)
This paper investigates a laser-powered UAV communication system. To maximize the minimum throughput among ground nodes, we jointly optimize communication scheduling, transmit power, and UAV trajectory. The resulting non-convex problem is decomposed into three subproblems and solved via successive convex approximation and iterative techniques. The simulation results show that our algorithm has fast and stable convergence.